2021
DOI: 10.1093/cvr/cvab117
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the transcriptome in cardiovascular disease

Abstract: The human transcriptome comprises a complex network of coding and non-coding RNAs implicated in a myriad of biological functions. Non-coding RNAs exhibit highly organised spatial and temporal expression patterns and are emerging as critical regulators of differentiation, homeostasis and pathological states, including in the cardiovascular system. This review defines the current knowledge gaps, unmet methodological needs and describes the challenges in dissecting and understanding the role and regulation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 117 publications
0
16
0
Order By: Relevance
“…We present a 14-gene signature that precisely classifies patients according to their pulmonary outcomes 3 months after hospital discharge. Since RNA-based biomarker in vitro assays are commercially available [55] , our results are clinically relevant. Profiling blood transcript abundance on a genome-wide scale emerges as a promising tool for the development of useful biomarkers for the management of “post-COVID” patients.…”
Section: Discussionmentioning
confidence: 90%
“…We present a 14-gene signature that precisely classifies patients according to their pulmonary outcomes 3 months after hospital discharge. Since RNA-based biomarker in vitro assays are commercially available [55] , our results are clinically relevant. Profiling blood transcript abundance on a genome-wide scale emerges as a promising tool for the development of useful biomarkers for the management of “post-COVID” patients.…”
Section: Discussionmentioning
confidence: 90%
“…The transcriptomes, genomes, and epigenomes from individual cells and cell types in complex heterogeneous organs and tissues of the CV are described through DNA and RNA technical sequencing. The miRNA-1254 levels predicted changes in the left ventricular (LV) volumes and LV ejection fraction 6 months after ST elevation MI (STEMI) [ 77 ].…”
Section: Microrna and Cu Metabolism In Disease Statesmentioning
confidence: 99%
“…Mutharasan and collaborators [ 77 , 125 ], demonstrated that miR-210 is upregulated through both HIF-dependent and independent pathways. In the HIF-1β knockout mouse, protein kinase B (AKT) increased the miR-210 levels under hypoxia.…”
Section: Microrna and Cu Metabolism In Disease Statesmentioning
confidence: 99%
“…Studies of non-coding transcriptome, which even though have limited protein-coding functions, are discovering the pathology of CVD. To eventually realize precision medicine, we are still facing the challenges of standardization of methodologies and translation 105 . In addition, researches in this area largely depend on the availability of tissues from autopsy, thus the clinical translation and implementation has been limited.…”
Section: Proteomics and Gene Expression Reveal The Interactions Between Cell Processes And External Environmentmentioning
confidence: 99%